Peran guru dalam membangun lingkungan belajar yang meiliki program inklusi dan memberikan semangat semua siswa - Saniyah, Rohmatur Robiatus (Maliki Interdisciplinary Journal, 2024)
The development of contemporary education is leaning towards an inclusive education model. The role of teachers in creating an inclusive learning environment and motivating all students is a crucial aspect of inclusive education. Inclusive education is an educational system that caters to children with certain limitations as well as other children, bringing them together without considering their individual limitations. In this context, teachers have the responsibility to create a learning environment that embraces student diversity and provides appropriate support for individuals. By understanding the needs and potential of each student, teachers can design inclusive and differentiated learning strategies. The role of teachers as motivators and encouragers is vital for the participation and engagement of all students in the learning process.